A Multi-centre Study to Evaluate the Long-Term Efficacy and Safety of Biosimilar Infliximab (Infimab™) in Ankylosing Spondylitis in Real-world Clinical Settings - A perspective from Eastern India - Pradip Kumar Sarma; Sukumar Mukherjee; R N Sarkar; Santosh Kumar Mandal; Pradeepta Patra; Tanoy Bose; Ajit Surin; Santa Naorem; Kaushik Basu; J.R. Parida; CT Arunachalam (International Journal of Medical Research and Review, 2022)
Introduction: Owing to dearth of data on infliximab biosimilars in Indian patients, a pan-India case database-based study with infliximab biosimilar BOW015 (Infimab™) was carried out to capture its efficacy and safety in real world clinical settings in India. Here, we assessed its efficacy and safety in ankylosing spondylitis (AS) among patients in the East India cohort.Materials and methods: Data were collected from multiple centers across the eastern region of India. Patients diagnosed with AS, within the preceding 4-6 months during the preceding one year were included in the study. Patients who were given BOW015 for other indications, prior innovator infliximab or other biologics were excluded from the study. Primary variable was Ankylosing Spondylitis Disease Activity Scale (ASDAS) response defined as change of > 2 in the ASDAS score from the baseline by 4-6 months of follow up.Results: The cohort consisted of 149 patients, predominantly male (69.8%), with mean (±SD) age of 36.75 (±11.11) years and mean (±SD) body weight of 58.26 (±15.4) kgs. Of the treated patients, 91 (61.1%) patients were administered four doses, 10 (6.7%) patients were administered three doses, 37 (24.8%) patients were administered two doses and 11 (7.4%) patients were administered only a single dose of BOW015. In the final analysis set, 81 patients had data at baseline and 4th visit. Among the 81 patients, 74 (91%) patients achieved major improvement, 5 (6%) patients achieved clinically important improvement and 2 (3%) were non-responders at 4th visit. Secondarily, cross categorization of the cohort into disease activity categories by number of infusions administered from baseline to 4th visit and assessment of trends in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores were also carried out and these too confirmed the efficacy of BOW015.Conclusion: Infimab™ (BOW015) showed significant improvement in ASDAS and BASDAI in patients with AS at the end of 4-6 months of follow up with its clinical benefits being apparent as early as first dose of BOW015.